2021
DOI: 10.1172/jci.insight.144619
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus oncolytic activity requires CD8+ T cells and is boosted by immune checkpoint blockade

Abstract: Glioblastoma multiforme (GBM) is a fatal human cancer in part because GBM stem cells are resistant to therapy and recurrence is inevitable. Previously, we demonstrated Zika virus (ZIKV) targets GBM stem cells and prevents death of mice with gliomas. Here, we evaluated the immunological basis of ZIKV-mediated protection against GBM. Introduction of ZIKV into the brain tumor increases recruitment of CD8 + T and myeloid cells to the tumor microenvironment. CD8 + T cells are required for ZIKV-dependent tumor clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 99 publications
2
47
0
Order By: Relevance
“…Antiviral immunity, inflammation, and apoptosis of GSCs are stimulated through virus infection (158). A recent in vivo study showed that CD8+ T cells were required for ZIKV oncolytic activity and immune checkpoint inhibitors could improve the effect of OVT (159). Cytosine phosphate-guanine (CpG) recoding of Zika viral genome can reduce virus infection kinetics in nonmalignant brain cells, but retains high infectivity and oncolysis in GSCs (160).…”
Section: Zika Virusmentioning
confidence: 99%
“…Antiviral immunity, inflammation, and apoptosis of GSCs are stimulated through virus infection (158). A recent in vivo study showed that CD8+ T cells were required for ZIKV oncolytic activity and immune checkpoint inhibitors could improve the effect of OVT (159). Cytosine phosphate-guanine (CpG) recoding of Zika viral genome can reduce virus infection kinetics in nonmalignant brain cells, but retains high infectivity and oncolysis in GSCs (160).…”
Section: Zika Virusmentioning
confidence: 99%
“…Moreover, ZIKV modified immune profiling in treated animals, inducing a local immunological response in the tumor mass [109]. In accordance, Nair S. et al showed that ZIKV treatment induces changes in the GBM microenvironment, increasing local recruitment of CD8 + T cells and myeloid cells, and thus contributing to tumor clearance and long-term protection from recurrence [110]. Similarly, Crane AT et al showed enhanced effector/memory CD4 + T cell responses in mice after ZIKV subcutaneous injection, suggesting the use of this virus as a potential adjuvant to vaccine-based immunotherapies against GBM [111].…”
Section: Zika and Glioblastomamentioning
confidence: 76%
“…For instance, some studies find that anti-CTLA-4 antibody monotherapy leads to 50% long-term survival of GL261-bearing mice, 78 while others show the intervention to not lead to any survival extension at all. 79 Relatedly, in the CT-2A glioma model, some researchers have observed up to 60% long-term survival following anti-PD-1 monotherapy 80 while most observe no survival benefit whatsoever. 28 , 81 We do not intend to cast doubt on the scientific practices or the honest work of our colleagues, but rather to contend that common and innocuous variations in the execution of a simple experiment can lead to drastically different conclusions.…”
Section: Discussionmentioning
confidence: 99%